DHR51, the Drosophila melanogaster homologue of the human photoreceptor cell-specific nuclear receptor, is a thiolate heme-binding protein. - de Rosny, E.; de Groot, A.; Jullian-Binard, C.; Borel, F.; Suarez, C.; Le Pape, L.; Fontecilla-Camps, J.C.; Jouve, H.M. (Biochemistry, 2008)
Heme has been recently described as a regulating ligand for the activity of the human nuclear receptors (NR) REV-ERBalpha and REV-ERBbeta and their Drosophila homologue E75. Here, we report the cloning, expression in Escherichia coli, purification, and screening for the heme-binding ability of 11 NR ligand-binding domains of Drosophila melanogaster (DHR3, DHR4, DHR39, DHR51, DHR78, DHR83, HNF4, TLL, ERR, FTZ-F1, and E78), of unknown structure. One of these NRs, DHR51, homologous to the human photoreceptor cell-specific nuclear receptor (PNR), specifically binds heme and exhibits a UV-visible spectrum identical to that of heme-bound E75-LBD. EPR and UV-visible absorption spectroscopy indicates that, like in E75, the heme contains a hexa-coordinated low spin ferric iron. One of its axial ligands is a tightly bound cysteine, while the other one is a histidine. A dissociation constant of 0.5 microM for the heme was measured by isothermal titration calorimetry. We show that DHR51 binds NO and CO and discuss the possibility that DHR51 may be either a gas or a heme sensor.